Defining business process improvement metrics based on BPM life cycle and process mining techniques. (22nd May 2019) - Lamghari, Zineb; Radgui, Maryam; Saidi, Rajaa; Rahmani, Moulay Driss
Nowadays, organisations use business process management (BPM) around the world to maintain a competitive advantage related to their business processes (BP). In this sense, business process improvement implies often a challenge in identifying specific improvement metrics according to the BP types, which from different scenarios. Thus, we present in this paper an integrated approach for defining improvement metrics according to the BP types. Our proposed approach is validated through a case study involving the enhancement of a BP. This BP is about requests for compensation within an airline company. Our approach consists of three main pillars: 1) management BP metrics; 2) operational BP metrics; 3) support BP metrics. In order to identify appropriate improvement interventions, modelling, analysis, simulation, monitoring and process mining techniques are used.